Isolating membrane, battery monomer, battery and electric device
Patent Information
- Application Number
- CN202380060952.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-17
- Publication Date
- 2025-04-08
AI Technical Summary
The cycle performance of existing battery cells is poor, especially during the charging and discharging process, they are prone to lack of liquid, which leads to increased polarization and shortened life.
A separator film including a polymer group is used. The polymer group is composed of polymers with high liquid absorption and high liquid retention capabilities. By using this isolation film in the battery cell, the liquid absorption rate and liquid retention capacity of the electrolyte are improved. , reduce the liquid shortage during the cycle charge and discharge process, and extend the battery life.
It effectively reduces the liquid shortage of battery cells during the cycle charge and discharge process, reduces polarization, and improves the cycle performance and life of battery cells.
Smart Images

Figure CN119790540A_ABST
Abstract
Description
Separator, battery cell, battery and electrical device Technical Field
[0001] The present application relates to the field of batteries, and in particular to an isolation membrane, a battery cell, a battery, and an electrical device. Background Art
[0002] Battery cells have the characteristics of high capacity and long life, and are therefore widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric airplanes, electric boats, electric toy cars, electric toy boats, electric toy airplanes and power tools, etc.
[0003] As battery applications become increasingly widespread, the requirements for battery cell performance are becoming increasingly stringent. However, the current cycle performance of battery cells is relatively poor and still needs to be further improved.
[0004] Summary of the Invention
[0005] The embodiments of the present application are made in view of the above-mentioned problems, and an object thereof is to provide a separator, a battery cell, a battery, and an electric device.
[0006] A first aspect of the present application provides a separator, comprising a polymer group, wherein the polymer group comprises at least one of a first polymer and a second polymer;
[0007] Wherein, the isolation film satisfies:
[0008] M represents the mass of the separator that does not absorb the electrolyte, and its unit is g;
[0009] m1 represents the mass of the separator measured at ambient pressure after being immersed in the electrolyte for 2 hours, and its unit is g;
[0010] m2 represents the mass of the separator measured at a pressure of 10000N in ambient pressure after being immersed in the electrolyte for 2 hours, and its unit is g;
[0011] v represents the liquid absorption rate of the isolation membrane, and its unit is mg / s;
[0012] λ represents the porosity of the separator.
[0013] Therefore, the isolation membrane of the embodiment of the present application includes a polymer group, and the polymer included in the polymer group has high liquid absorption and high liquid retention capabilities. On the one hand, the isolation membrane has a strong liquid retention capacity, and the electrolyte is not easily squeezed out during the cyclic charge and discharge process of the battery cell; on the other hand, the isolation membrane has a strong liquid absorption capacity and a fast liquid absorption rate. Even if a small amount of electrolyte is squeezed out, it can be quickly absorbed back during the discharge process of the battery cell, and the transmission rate of the electrolyte between the isolation membrane and the electrode is accelerated, thereby reducing the liquid shortage during the cyclic charge and discharge process, reducing battery polarization, and improving the cycle performance of the battery cell.
[0014] In some embodiments, the isolation film satisfies:
[0015] Therefore, when the isolation membrane of the embodiment of the present application meets the above conditions, its liquid absorption and liquid retention capabilities can be further improved, which can further reduce liquid shortage during cyclic charge and discharge, reduce battery polarization, and improve the cycle performance of the battery cell.
[0016] In some embodiments, the isolation film satisfies:
[0017] Optionally,
[0018] Therefore, when the isolation membrane of the embodiment of the present application meets the above conditions, its liquid absorption and liquid retention capabilities can be further improved, which can further reduce liquid shortage during cyclic charge and discharge, reduce battery polarization, and improve the cycle performance of the battery cell.
[0019] In some embodiments, the isolation film satisfies:
[0020] Therefore, when the isolation membrane of the embodiment of the present application meets the above conditions, its liquid absorption and liquid retention capabilities can be further improved, which can further reduce liquid shortage during cyclic charge and discharge, reduce battery polarization, and improve the cycle performance of the battery cell.
[0021] In some embodiments, the isolation film satisfies:
[0022] Therefore, when the isolation membrane of the embodiment of the present application meets the above conditions, its liquid absorption and liquid retention capabilities can be further improved, which can further reduce liquid shortage during cyclic charge and discharge, reduce battery polarization, and improve the cycle performance of the battery cell.
[0023] In some embodiments, the isolation film satisfies:
[0024] v / λ>5.00; optionally, 5<v / λ<50.
[0025] Therefore, when the separator of the embodiment of the present application meets the above conditions, the liquid absorption capacity of the separator is relatively good, which is conducive to improving the absorption rate of the electrolyte, thereby further improving the cycle performance of the battery cell.
[0026] In some embodiments, the mass percentage of the polymer group is 0.1% to 20% based on the total mass of the separator. When the mass percentage of the polymer group is within the above range, the separator has relatively good liquid absorption and liquid retention capabilities, which is conducive to further improving the cycle performance of the battery cell.
[0027] In some embodiments, the first polymer and the second polymer each independently comprise a fluorinated polymer.
[0028] Optionally, the crystallinity of the fluoropolymer measured by differential scanning calorimetry is Xc1, 0<Xc1≤30%; the melting temperature of the fluoropolymer is T m1 , its unit is ℃, 0<T m1 ≤140.
[0029] In some embodiments, the glass transition temperature of the fluorinated polymer is T g1 , its unit is ℃, -150≤T g1 ≤60.
[0030] In some embodiments, the fluorinated polymer comprises at least one of the structural units represented by formula (AI) to the structural units represented by formula (AIII),
[0031] In formula (AI) and formula (AII), R 11 、R 12 、R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a bromine atom, a substituted or unsubstituted C1-C3 alkyl group or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 、R 12 、R 13 and R 14 At least one of them contains a fluorine atom;
[0032] In formula (AIII),
[0033] R 15 including a single bond, a substituted or unsubstituted C1-C3 alkyl group; p is a positive integer selected from 1 to 3; and n is a positive integer selected from 1,000 to 30,000.
[0034] In some embodiments, the liquid-retaining polymer further comprises an ether polymer, wherein the ether polymer is made into a sheet structure; the sheet structure is (T m2 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K1, 1<K1<∞, T m2 ℃ represents the melting temperature of the ether polymer; optionally, 1<K1≤100; further optionally, 1<K1≤10.
[0035] In some embodiments, the first polymer and the second polymer each independently comprise an ether polymer.
[0036] Optionally, the ether polymer includes a structural unit represented by formula (BI) and / or a structural unit represented by formula (BII),
[0037] In formula (BI), R 21 and R 22 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; R 23 Including substituted or unsubstituted C1-C5 alkylene;
[0038] In formula (BII), R 24 to R 27 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 alkoxy group or an ether group, and R 24 to R 27 At least one of them contains a substituted or unsubstituted C1-C3 alkoxy group or an ether group.
[0039] In some embodiments, the first polymer and the second polymer each independently comprise an ester polymer.
[0040] Optionally, the ester polymer is made into a sheet structure; the sheet structure is (T m3 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K2, 1<K2<∞, T m3 ℃ represents the melting temperature of the ester polymer; optionally, 1<K2≤100; further optionally, 1<K2≤10.
[0041] In some embodiments, the ester polymer includes a structural unit represented by formula (CI) and / or a structural unit represented by formula (CII),
[0042] In formula (CI), R 31 、R 32 and R 33 Each independently includes a hydrogen atom, or a substituted or unsubstituted C1-C8 alkyl group; R 34 Including substituted or unsubstituted C1-C8 alkyl, or substituted or unsubstituted C1-C8 hydroxyalkyl;
[0043] In formula (CII), R 35 including substituted or unsubstituted C2-C6 methylene; optionally, R 35 Each independently includes a substituted or unsubstituted C2-C4 methylene group.
[0044] In some embodiments, the first polymer and the second polymer each independently comprise an aldehyde-ketone polymer.
[0045] Optionally, the aldehyde-ketone polymer is made into a sheet structure; the sheet structure is (T m4 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K3, 0.8≤K3<∞, T m4 ℃ represents the melting temperature of the aldehyde-ketone polymer; optionally, 0.8≤K3≤100; further optionally, 0.8≤K3≤10.
[0046] In some embodiments, the aldehyde-ketone polymer comprises a structural unit represented by formula (DI) and / or a structural unit represented by formula (DII),
[0047] In formula (DI), R 41 Including single bonds, substituted or unsubstituted C1-C6 methylene; R 42 including hydrogen atoms, substituted or unsubstituted C1-C6 alkyl groups;
[0048] In formula (DII), R 43 to R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from an integer from 0 to 5, and at least one of r and s is selected from a positive integer.
[0049] In some embodiments, the molecular weight of the liquid retaining polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.
[0050] In some embodiments, the isolation body includes a substrate, and the polymer layer is disposed on at least one surface of the substrate.
[0051] In some embodiments, the isolation membrane includes a porous substrate, and the polymer group is distributed in the pores of the porous substrate.
[0052] In some embodiments, the isolation membrane includes a porous substrate and a polymer layer disposed on at least one surface of the porous substrate, wherein the polymer layer includes the polymer group.
[0053]
[0054] In some embodiments, the coating weight of the polymer group is 0.5 mg / 1540.25 mm 2 Up to 5mg / 1540.25mm 2 .
[0055] In a second aspect, the present application proposes a battery cell comprising an isolation membrane as described in any embodiment of the first aspect of the present application.
[0056] In a third aspect, the present application proposes a battery comprising a battery cell as described in any embodiment of the second aspect of the present application.
[0057] In a fourth aspect, the present application proposes an electrical device comprising a battery as described in any embodiment of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0059] FIG1 is a schematic diagram of a battery cell according to an embodiment of the present application.
[0060] FIG. 2 is an exploded schematic diagram of an embodiment of the battery cell of FIG. 1 .
[0061] FIG3 is a schematic diagram of an embodiment of a battery module of the present application.
[0062] FIG4 is a schematic diagram of an embodiment of a battery pack of the present application.
[0063] FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 .
[0064] FIG6 is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.
[0065] The drawings are not necessarily drawn to scale.
[0066] The accompanying drawings are described as follows: 1. battery pack; 2. upper case; 3. lower case; 4. battery module; 5. battery cell; 51. housing; 52. electrode assembly; 53. cover plate; 6. electrical device. DETAILED DESCRIPTION
[0067] The following detailed description specifically discloses the embodiments of the separator, battery cell, battery, and electrical device of the present application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially identical structures may be omitted. This is to avoid unnecessary length in the following description and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0068] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0069] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. Unless otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0070] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may further include step (c), which indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.
[0071] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may indicate that other components not listed may also be included or that only the listed components are included.
[0072] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0073] In this application, the terms "plurality" and "multiple" refer to two or more.
[0074] The term "alkyl" encompasses both straight and branched chain alkyl groups. For example, the alkyl group may be a C1-C5 alkyl group, a C1-C4 alkyl group, a C1-C3 alkyl group, or a C1-C2 alkyl group. In some embodiments, the alkyl group includes a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, and the like. Additionally, the alkyl group may be optionally substituted. When substituted, the substituent includes a fluorine atom.
[0075] The term "alkoxy" refers to a group in which an alkyl group is connected to an oxygen atom by a single bond. For example, the alkoxy group can be a C1 to C5 alkoxy group, a C1 to C3 alkoxy group, or a C1 to C2 alkoxy group. In some embodiments, the alkoxy group can include a methoxy group, an ethoxy group, or a propoxy group. In addition, the alkoxy group can be optionally substituted.
[0076] The term "halogen atom" refers to a fluorine atom, a chlorine atom, a bromine atom or the like.
[0077] The term "hydrogen" refers to 1H (protium, H), 2H (deuterium, D), or 3H (tritium, T). In various embodiments, "hydrogen" may be 1H (protium, H).
[0078] A battery cell consists of a positive electrode, a negative electrode, a separator, and an electrolyte. The separator is located between the positive and negative electrodes to isolate them from each other. During the charge and discharge cycles of a battery cell, the electrode assembly expands in volume. This expansion force is particularly high in the later stages of a battery cell cycle, causing the electrolyte to be squeezed out. The separator's slow liquid absorption rate makes electrolyte reabsorption difficult, increasing the risk of electrode shortfalls and bridge failure. This can worsen the battery cell's cycle performance and shorten its cycle life.
[0079] In view of the above problems, the embodiment of the present application proposes an isolation membrane, which includes a polymer group. The polymer included in the polymer group has high liquid absorption and high liquid retention capabilities. On the one hand, the isolation membrane has a strong liquid retention capacity, and the electrolyte is not easily squeezed out during the cyclic charge and discharge process of the battery cell; on the other hand, the isolation membrane has a strong liquid absorption capacity and a fast liquid absorption rate. Even if a small amount of electrolyte is squeezed out, it can be quickly absorbed back during the discharge process of the battery cell, and the transmission rate of the electrolyte between the isolation membrane and the electrode is accelerated, thereby reducing the liquid shortage during the cyclic charge and discharge process, reducing battery polarization, and improving the cycle performance of the battery cell.
[0080] Isolation film
[0081] In a first aspect, an embodiment of the present application provides an isolation film, wherein the isolation film includes a polymer group, wherein the polymer group includes at least one of a first polymer and a second polymer; the isolation film satisfies:
[0082] M represents the unit of g;
[0083] m1 represents the mass of the separator measured at ambient pressure after being immersed in the electrolyte for 2 hours, and its unit is g;
[0084] m2 represents the mass of the separator after being immersed in the electrolyte for 2 hours and under a force of 10000N at ambient pressure, and its unit is g;
[0085] v represents the liquid absorption rate of the isolation membrane, and its unit is mg / s;
[0086] λ represents the porosity of the separator.
[0087] When the above formula is used for specific calculations, only the specific values are taken into account, without taking into account the units of the parameters.
[0088] The isolation membrane of the embodiment of the present application includes a polymer group, and the polymer included in the polymer group has high liquid absorption and high liquid retention capabilities. On the one hand, the isolation membrane has a strong liquid retention capacity, and the electrolyte is not easily squeezed out during the cyclic charge and discharge process of the battery cell; on the other hand, the isolation membrane has a strong liquid absorption capacity and a fast liquid absorption rate. Even if a small amount of electrolyte is squeezed out, it can be quickly absorbed back during the discharge process of the battery cell, and the transmission rate of the electrolyte between the isolation membrane and the electrode is accelerated, thereby reducing the liquid shortage during the cyclic charge and discharge process, reducing battery polarization, and improving the cycle performance of the battery cell.
[0089] The separator can be made from a substrate and a polymer group. Alternatively, the separator is derived from a battery cell. The battery cell is disassembled, and the separator soaked in the electrolyte is removed from the battery cell. The separator is then rinsed with deionized water and vacuum-dried at 80°C for 12 hours to obtain the separator. This separator is then used for separator tests such as mass weighing, liquid absorption rate, and porosity.
[0090] M represents the mass of the separator that has not absorbed the electrolyte, which can also be understood as the mass of the separator itself. Specifically, the separator can be cut into 10 pieces of 1540.25mm 2 The mass of the disc is weighed on an electronic balance.
[0091] m1 represents the mass of the separator after being immersed in the electrolyte for 2 hours and weighed at ambient pressure. Specifically, the separator can be cut into 10 pieces of 1540.25 mm 2 After immersing the disc in the electrolyte for 2 hours, take out the disc and weigh it after hanging it in the air for 2 minutes under ambient pressure.
[0092] m2 represents the mass of the separator after it is immersed in the electrolyte for 2 hours and then weighed under a force of 10000N in ambient pressure. Specifically, the separator can be cut into 10 pieces of 1540.25mm 2 After immersing the disc in the electrolyte for 2 hours, the disc is taken out and stacked in sequence. After applying a force of 10000N under ambient pressure, the mass of the isolation membrane is weighed.
[0093] This application is tested using a standard electrolyte as a test sample. The specific formula of the electrolyte can refer to the electrolyte formula in the embodiment. For example, the electrolyte includes ethylene carbonate EC, ethyl methyl carbonate EMC, and dimethyl carbonate DMC in a volume ratio of 1:1:1, and the electrolyte also includes lithium hexafluorophosphate LiPF6 with a molar concentration of 1 mol / L.
[0094] In the embodiment of the present application, v represents the liquid absorption rate of the isolation membrane, which can be detected by the following method. The specific steps are as follows:
[0095] Use a pipette to draw 1 mL of electrolyte;
[0096] Cut the isolation film into 1540.25mm 2 Small discs are placed horizontally in the air;
[0097] Place 1 mL of electrolyte solution on the center of the small disc using a pipette, and start timing to record the time when the electrolyte wetting radius reaches 10 mm.
[0098] The ratio of the wetting radius to the wetting time was calculated to obtain the liquid absorption rate v.
[0099] This application uses standard electrolyte as the test sample for testing. The specific formula of the electrolyte can refer to the electrolyte formula in the examples.
[0100] In an embodiment of the present application, the porosity of the isolation membrane is the ratio of the pore volume in the isolation membrane to the overall volume of the isolation membrane, and can be detected using equipment and methods known in the art, for example, according to GB / T21650.2-2008 "Determination of pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method Part 2: Analysis of mesopores and macropores by gas adsorption method" and ASTMD2873-94el "Standard Test Method for Interior Porosity of Poly(Vinyl Choride)(PVC)Resins by Mercury Intrusion Porosimetry".
[0101] In some embodiments, the isolation film satisfies:
[0102] When the separator meets the above conditions, its liquid absorption and liquid retention capabilities can be further improved, which can further reduce the lack of liquid during the cyclic charge and discharge process, reduce battery polarization, and improve the cycle performance of the battery cell.
[0103] For example, It can be 1.5, 2.0, 2.5, 3.0, 3.2, 3.5, 3.8, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 12, or a range consisting of any two of the above values.
[0104] In some embodiments, the isolation film satisfies:
[0105] m2-M represents the mass of the isolating membrane weighed under a pressure of 10,000 N in ambient pressure after being immersed in the electrolyte for 2 hours, and the difference between the mass of the isolating membrane without absorbing the electrolyte, that is, m2-M is the amount of liquid retained by the isolating membrane under external action, which can characterize the liquid retention capacity of the isolating membrane.
[0106] m1-M represents the mass of the separator weighed at ambient pressure after being immersed in the electrolyte for 2 hours, and the difference between the mass of the separator without absorbing the electrolyte, that is, m1-M is the amount of liquid absorbed by the separator, which can characterize the liquid absorption capacity of the separator.
[0107] It can be defined as the liquid retention capacity Λ.
[0108] When the separator meets the above conditions, the separator has strong liquid absorption and liquid retention capabilities, which can reduce liquid shortage during cyclic charge and discharge, reduce battery polarization, and improve the cycle performance of battery cells.
[0109] Optionally,
[0110] For example, It can be:
[0111] 25.1%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, 36%, 36.5%, 37%, 37.5%, 38%, 39 %, 40%, 41%, 42%, 45%, 46%, 48%, 50%, 52%, 55%, 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88%, 90%, 92%, 95%, 96%, 97%, 98%, 99% or a range consisting of any two of the above values.
[0112] In some embodiments, the isolation film satisfies:
[0113] m1-M represents the ratio of the amount of liquid absorbed by the isolation membrane to the mass of the isolation membrane itself, which can characterize the liquid absorption capacity of the isolation membrane. It can indicate the amount of electrolyte absorbed by the isolation membrane, and its liquid retention capacity can also be relatively improved.
[0114] It can be defined as the liquid retention rate of the isolation membrane.
[0115] When the separator meets the above conditions, the liquid absorption capacity of the separator is relatively good, which is beneficial to improving the absorption rate of the electrolyte, thereby further improving the cycle performance of the battery cell.
[0116] For example, It can be:
[0117] 88%, 90%, 92%, 95%, 96%, 97%, 98%, 99%, 100%, 105%, 110%, 120%, 130%, 140%, 150%, 160%, 170%, 180%, 190%, 200%, 210%, 220%, 230%, 240%, 250%, 260%, 270%, 280%, 290%, 300% or a range consisting of any two of the above values.
[0118] In some embodiments, the isolation film satisfies:
[0119] (m2-M) / M represents the ratio of the amount of liquid retained by the isolation membrane under external action to the mass of the isolation membrane itself, which can characterize the liquid retention capacity of the isolation membrane.
[0120] It can be defined as the liquid retention rate after the isolation membrane is pressurized.
[0121] When the separator meets the above conditions, under pressurized conditions, the separator has a relatively good liquid retention capacity, and the electrolyte adsorbed by the separator is not easily squeezed out, thereby increasing the migration rate of active ions and further improving the cycle performance of the battery cell.
[0122] For example, It can be:
[0123] 22.5%, 25.1%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, 36%, 36.5%, 37%, 37.5%, 38%, 39%, 40%, 41%, 42%, 45%, 46%, 48%, 50%, 52%, 55%, 60%, 62%, 65%, 68 %, 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88%, 90%, 92%, 95%, 96%, 97%, 98%, 99%, 100%, 105%, 110%, 120%, 130%, 140%, 150%, 160%, 170%, 180%, 190%, 200%, 210%, 220%, 230%, 240%, 250%, 260%, 270%, 280%, 290%, 300% or a range consisting of any two of the above values.
[0124] In some embodiments, v / λ>5.00; alternatively, 5<v / λ<50.
[0125] When the separator meets the above conditions, the liquid absorption capacity of the separator is relatively good, which is beneficial to improving the absorption rate of the electrolyte, thereby further improving the cycle performance of the battery cell.
[0126] Illustratively, v / λ may be 5.1, 5.2, 5.5, 6, 6.5, 7, 8, 9, 10, 12, 15, 18, 20, 25, 30, 35, 40, 45, 46, 47, 48, 49, 49.5, 50, 55, or a range consisting of any two of the above values.
[0127] Based on the total mass of the isolation film, the mass percentage of the polymer group is 0.1% to 20%.
[0128] When the mass percentage of the polymer group is within the above range, the separator has relatively good liquid absorption and liquid retention capabilities, which is beneficial to further improve the cycle performance of the battery cell.
[0129] Illustratively, the mass percentage of the polymer group can be 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 1.5%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, 11.0%, 12.0%, 13.0%, 14.0%, 15.0%, 16.0%, 17.0%, 18.0%, 19.0%, 20.0% or a range consisting of any two of the above values.
[0130] The first polymer and the second polymer may be made of the same material or different materials. The first polymer may be a highly liquid-absorbing polymer, and the second polymer may be a highly liquid-retaining polymer.
[0131] When the first polymer and the second polymer are selected from the same material, the material can have both liquid absorption and liquid retention capabilities.
[0132] When the first polymer and the second polymer are made of different materials, the first polymer may have a higher liquid absorption capacity than the second polymer, and the second polymer may have a higher liquid retention capacity than the first polymer. Alternatively, the first polymer may include at least one of an ether polymer and an ester polymer. Alternatively, the second polymer may include at least one of a fluorinated polymer and an aldehyde or ketone polymer.
[0133] The first polymer and the second polymer may be independently selected from at least one of fluorinated polymers, ether polymers, ester polymers, and aldehyde-ketone polymers.
[0134] In some embodiments, the first polymer and the second polymer each independently comprise a fluorinated polymer having a crystallinity of X as measured by differential scanning calorimetry.C1 ,0<X C1 ≤30%; the melting temperature of the fluoropolymer is T m1 , its unit is ℃, 0<T m1 ≤140.
[0135] Crystallization refers to the process in which atoms, ions or molecules in a material are arranged in a certain spatial order to form an orderly structure. The conformation of the polymer in the crystallization is determined by both intramolecular and intermolecular factors. The intermolecular force will affect the packing density between molecular chains. C1 It is used to characterize the degree of crystallinity in the material, which can be measured by differential scanning calorimetry (DSC). Specifically, the test steps are as follows: take 0.5g to 0.8g of sample, place the sample in a carrier crucible, and perform temperature rise and fall treatment on the sample under a nitrogen atmosphere, with a heating rate of 10℃ / min from the intrinsic T g1 The initial temperature is 20℃ lower and then heated to the intrinsic T m1 The cut-off temperature of the process is 20℃ higher. The actual glass transition temperature T of the material is determined according to the endothermic and exothermic peak or transition point of the material in the process. g1 and melting temperature T m1 wait.
[0136] As a result, fluoropolymers have relatively low crystallinity and melting temperature, which makes the molecular chains tend to be loose, the interaction force between the molecular chains is small, adjacent molecular chains are easily opened, and the chain segment movement is achieved through intermolecular rotation, forming a molecular chain structure with high flexibility; and the fluoropolymers and the electrolyte in the battery cell can form a gel-like substance, thereby improving the cycle performance of the battery cell.
[0137] For example, the crystallinity X of the fluorinated polymer measured by differential scanning calorimetry is C1 It can be 5%, 10%, 15%, 20%, 25%, 30% or a range consisting of any two of the above values.
[0138] For example, the melting temperature of the fluorinated polymer may be 10° C., 20° C., 50° C., 70° C., 90° C., 100° C., 120° C., 140° C., or a range consisting of any two of the foregoing values.
[0139] In some embodiments, the glass transition temperature of the fluorinated polymer is T g1 , its unit is ℃, -150≤T g1 ≤60.
[0140] The glass transition temperature is the temperature at which the chain segments of a polymer transition from freezing to movement. The glass transition temperature has a certain influence on the flexibility of the polymer molecular chain. The lower the glass transition temperature, the better the flexibility of the polymer molecular chain at room temperature. The higher the glass transition temperature, the worse the flexibility of the molecular chain at room temperature. The glass transition temperature can be measured by differential scanning calorimetry (DSC). The lower the glass transition temperature of a polymer, the better the segment flexibility of the molecular chain, and the easier it is for adjacent molecular chains to be opened. For example, the glass transition temperature of a fluorinated polymer can be -150°C, -120°C, -100°C, -80°C, -60°C, -30°C, 0°C, 30°C, 60°C, or a range consisting of any two of the above values.
[0141] In some embodiments, the fluorinated polymer comprises a structural unit represented by formula (AI),
[0142] In formula (AI), R 11 、R 12 、R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a bromine atom, a substituted or unsubstituted C1-C3 alkyl group or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 、R 12 、R 13 and R 14 At least one of them contains a fluorine atom.
[0143] In some embodiments, the fluorinated polymer comprises a structural unit represented by formula (AII),
[0144] In formula (AI) and formula (AII), R 11 、R 12 、R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a bromine atom, a substituted or unsubstituted C1-C3 alkyl group or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 、R 12 、R 13 and R 14 At least one of them contains a fluorine atom.
[0145] In some embodiments, the fluorinated polymer comprises a structural unit represented by formula (AII),
[0146] In formula (AIII), R 15 This includes single bonds, substituted or unsubstituted C1-C3 alkyl groups.
[0147] When the above-mentioned groups are substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom. The above-mentioned substituents are high-pressure resistant substituents, which are more conducive to stabilizing the structure of the polymer. The halogen atom may include a fluorine atom, a chlorine atom, a bromine atom, etc. Alternatively, the halogen atom includes a fluorine atom.
[0148] In the embodiments of the present application, the polymer may also be obtained by copolymerizing the above structural groups with a small amount of other types of structural groups (such as olefin structural units, ester monomers, nitrile monomers, amide monomers, etc.).
[0149] In some embodiments, p is a positive integer selected from 1 to 3.
[0150] In some embodiments, the degree of polymerization n of the fluorinated polymer is selected from a positive integer ranging from 1,000 to 30,000.
[0151] In some embodiments, R 11 、R 12 、R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a bromine atom, a substituted or unsubstituted C1-C2 alkyl group or a substituted or unsubstituted C1-C2 alkoxy group; further optionally, R 11 、R 12 、R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, a fluoromethyl group, a methoxy group or a perfluoromethoxy group.
[0152] In some embodiments, the fluorinated polymer includes at least one of the structural units represented by formula (AI-1) to the structural units represented by formula (AI-11),
[0153] In some embodiments, the fluorinated polymer includes at least one of the structural units represented by formula (AII-1) to the structural units represented by formula (AII-5),
[0154] In some embodiments, the fluorinated polymer includes at least one of the structural units represented by formula (AIII-1) to the structural units represented by formula (AIII-3),
[0155] Illustratively, the fluorinated polymer includes one or more of polyperfluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroethylene propylene copolymer (FEP), perfluoroalkoxy polymer (PFA), perfluoropolyether (PFPE), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE) and perfluoro (1-butenyl vinyl ether) polymer (CYTOP for short).
[0156] Optionally, the fluorinated polymer includes one or more of polyperfluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroethylene propylene copolymer (FEP), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), and polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE).
[0157] The fluoropolymer may be derived from one or more of the following monomers: fluorocycloethane, vinyl fluoride, 1,2-difluoroethylene, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene, 3,3,3-trifluoropropylene, trifluoropropylene, tetrafluoropropylene, and pentafluoropropylene. Alternatively, the fluoropolymer may be derived from at least two of the following monomers: fluorocycloethane, vinyl fluoride, 1,2-difluoroethylene, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene, 3,3,3-trifluoropropylene, trifluoropropylene, tetrafluoropropylene, and pentafluoropropylene.
[0158] The monomers used in the above-mentioned fluorinated polymers are all short-chain monomers, which are conducive to polymerization to form straight-chain linear structures or short-chain branched structures. This type of structure has a low degree of entanglement, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte, thereby facilitating the formation of a three-dimensional gel-like substance between the polymer and the electrolyte, which is conducive to further improving the liquid absorption rate.
[0159] In some embodiments, the fluorinated polymer n is selected from a positive integer ranging from 5,000 to 20,000.
[0160] In some embodiments, the molecular weight of the fluorinated polymer is 1.2×10 5 g / mol to 1.5×10 6 g / mol; optional: 1.2×10 5 g / mol to 1.0×10 6g / mol. When the molecular weight of the polymer is within the above range, it can ensure that the polymer exhibits a certain solubility in the electrolyte, while not being easily completely dissolved and dispersed by the electrolyte, which is beneficial to regulating the distribution and dispersion of the polymer; and it can further improve the flexibility between the molecular chains of the polymer. The interaction force between the molecular chains is relatively weak, which is beneficial for the solvent molecules in the electrolyte to open the molecular chains, enter between the molecular chains, and be wrapped by the molecular chains, thereby facilitating the active ions to enter the active substance through the solvent, realizing the smooth and rapid migration of the active ions. The polymer within the above molecular weight range is beneficial to improving the liquid absorption rate and liquid retention capacity of the isolation membrane.
[0161] For example, the molecular weight of the polymer may be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.5×10 6 g / mol or a range consisting of any two of the above values.
[0162] [Ether polymers]
[0163] In some embodiments, the first polymer and the second polymer each independently include an ether polymer, and the ether polymer is made into a sheet structure; the sheet structure is (T m2 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K1, 1<K1<∞, T m2 °C represents the melting temperature of the ether polymer.
[0164] Specifically, the sheet structure is prepared as follows: the ether polymer is vacuum dried at 80°C for 12 hours. The dried ether polymer is hot-pressed into a sheet by a flat vulcanizer, and the hot-pressing temperature is set to (T m2 The sample is then removed from the press after 2 minutes of calendering and placed on another vulcanizing press of the same model for cold pressing at a pressure of 10 MPa. A polymer disc (sheet structure) of fixed size is obtained using a circular mold with a diameter of 25 mm. For example, the sheet structure can be a disc with a thickness of 1-2 mm and a diameter of 25 mm; alternatively, a sample can be prepared according to the sample standard required by the test equipment.
[0165] According to the conclusions of classical linear viscoelasticity, for polymers, especially linear polymers, the elastic modulus G'-dissipation modulus G" in the terminal region of the elastic modulus G'-dissipation modulus G" curve (the interval approaching the maximum angular velocity) conforms to frequency dependence, and the longest chain of the polymer plays a role in the viscoelastic behavior.
[0166] The specific steps of the dynamic frequency sweep test are as follows: The dynamic frequency sweep test was performed using a TA-AR2000EX rotational rheometer (TAinstruments, USA) with a parallel plate diameter of 25 mm and a thickness of 0.9 mm. To ensure that the test was in the linear point-bounce region, the strain during the dynamic frequency sweep test was 2% and the test temperature was T m2 +20℃, test frequency sweep range: 500rad / s≤w 2 ≤0.05rad / s, so as to obtain data in the lowest possible frequency range.
[0167] The dynamic frequency sweep test can characterize the degree of entanglement of molecular chains under solid-phase melting (melt state). Compared with linear structures or short-chain branched structures, long-branched structures, network structures, and low-crosslinked structures have a high degree of entanglement, which will show deviation from linear terminal behavior. Ether polymers exhibit solid-phase behavior. When the ether polymers of the present application meet the above range, the entanglement state of the molecular chains can be further reduced, which is conducive to the diffusion of solvent molecules in the electrolyte between the molecular chains; moreover, the ether polymers still maintain a certain degree of molecular chain entanglement and can form a gel-like substance with the electrolyte, thereby improving the cycle performance and storage performance of the battery cell.
[0168] In some embodiments, 1<K1≤100; alternatively, 1<K1≤10. For example, K1 can be 1.01, 1.1, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000, or a range consisting of any two of the above values.
[0169] In some embodiments, the glass transition temperature of the ether polymer is T g2 , its unit is ℃, -100≤T g2 ≤50; optionally, -80≤T g2 ≤30. For example, the glass transition temperature of the ether polymer may be -100°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range consisting of any two of the above values.
[0170] In some embodiments, the ether polymer includes a structural unit represented by formula (BI),
[0171] In formula (BI), R 21 and R22 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; R 23 This includes substituted or unsubstituted C1-C5 methylene groups.
[0172] In some embodiments, R 21 and R 22 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C2 alkyl group.
[0173] In some embodiments, R 23 It includes single bonds, substituted or unsubstituted C1-C4 methylene groups.
[0174] Illustratively, the ether polymer includes at least one of the structural units represented by formula (BI-1) to the structural units represented by formula (BI-8),
[0175] In some embodiments, the ether polymer includes a structural unit represented by formula (BII),
[0176] In formula (BII), R 24 to R 27 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 alkoxy group or an ether group, and R 24 to R 27 At least one of them contains a substituted or unsubstituted C1-C3 alkoxy group or an ether group.
[0177] In some embodiments, R 24 to R 27 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C2 alkyl group, a substituted or unsubstituted C1-C2 alkoxy group or an ether group, and R 24 to R 27 At least one of them contains a substituted or unsubstituted C1-C2 alkoxy group or an ether group.
[0178] In some embodiments, the ether polymer includes at least one of the structural units represented by formula (BII-1) to the structural units represented by formula (BII-7),
[0179] The monomers used in the above-mentioned ether polymers are polycyclic rings, such as structures with six or less members, or short-chain monomers, which are conducive to the polymerization to form a high-content -O- structure. This type of structure has a low degree of entanglement, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte and easily form a gel-like substance with the electrolyte, thereby improving the cycle performance and storage performance of the battery monomer.
[0180] The above-mentioned polymers are only examples of the structural groups of the main molecular chain. In the embodiments of the present application, the polymers can also be obtained by copolymerizing the above-mentioned structural groups with other types of structural groups (such as olefin structural units, ester monomers, nitrile monomers, amide monomers and other structural units).
[0181] When the above-mentioned groups are substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom. These substituents are high-pressure-resistant substituents, which are more conducive to stabilizing the structure of the polymer. Halogen atoms may include fluorine atoms, chlorine atoms, bromine atoms, and the like.
[0182] In some embodiments, the degree of polymerization n of the ether polymer is a positive integer selected from 1,500 to 25,000.
[0183] Optionally, the polymerization degree n of the ether polymer is a positive integer selected from 3,000 to 18,000.
[0184] In some embodiments, the molecular weight of the polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.
[0185] For example, the molecular weight of the polymer may be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol or a range consisting of any two of the above values.
[0186] [Ester polymer]
[0187] In some embodiments, the first polymer and the second polymer each independently comprise an ester polymer, wherein the ester polymer is made into a sheet structure; the sheet structure is (T m3 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K2, 1<K2<∞, T m3 °C represents the melting temperature of the ester polymer.
[0188] When the ester polymer of the embodiment of the present application meets the above range, the entanglement state of the molecular chains can be further reduced, which is beneficial to the diffusion of solvent molecules in the electrolyte between the molecular chains; and the ether polymer still maintains a certain molecular chain entanglement state, can form a gel-like substance with the electrolyte, can increase the liquid absorption rate, and thereby improve the cycle performance and storage performance of the battery cell.
[0189] In some embodiments, 1<K2≤100; optionally, 1<K2≤10.
[0190] Illustratively, K2 may be 1.01, 1.1, 1.2, 1.5, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000, or a range consisting of any two of the above values.
[0191] In some embodiments, the glass transition temperature of the ester polymer is T g3 , its unit is ℃, -100≤T g3 ≤50; optionally, -80≤T g3 ≤30.
[0192] For example, the glass transition temperature of the ester polymer may be -100°C, -90°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range consisting of any two of the above values.
[0193] In some embodiments, the ester polymer comprises a structural unit represented by formula (CI),
[0194] In formula (CI), R 31 、R 32 and R 33 Each independently includes a hydrogen atom, or a substituted or unsubstituted C1-C8 alkyl group; R 34 Including substituted or unsubstituted C1-C8 alkyl, or substituted or unsubstituted C1-C8 hydroxyalkyl; optionally, R 34 It includes substituted or unsubstituted C1-C6 alkyl groups, or substituted or unsubstituted C1-C6 hydroxyalkyl groups.
[0195] Optionally, R 31 This includes a hydrogen atom, or a substituted or unsubstituted methyl group.
[0196] Optionally, R 32 and R 33 Each independently includes a hydrogen atom.
[0197] Optionally, R 34It includes substituted or unsubstituted C1-C4 alkyl groups, or substituted or unsubstituted C1-C4 hydroxyalkyl groups.
[0198] Illustratively, the ester polymer includes at least one of the structural units represented by formula (CI-1) to the structural units represented by formula (CI-15),
[0199] In some embodiments, the ester polymer comprises a structural unit represented by formula (CII),
[0200] In formula (CII), R 35 This includes substituted or unsubstituted C2-C6 methylene groups.
[0201] Optionally, R 35 Each independently includes a substituted or unsubstituted C2-C4 methylene group.
[0202] Illustratively, the ester polymer includes at least one of the structural units represented by formula (CII-1) to the structural units represented by formula (CII-5),
[0203] The molecular chains of the above-mentioned ester polymers have a low degree of entanglement, which is conducive to improving the flexibility of the molecular chains. The molecular chains can fully stretch in the electrolyte and easily form a gel-like substance with the electrolyte.
[0204] The above-mentioned polymers are only examples of the structural groups of the main molecular chain. In the embodiments of the present application, the polymers can also be obtained by copolymerizing the above-mentioned structural groups with other types of structural groups (such as olefin structural units, ester monomers, nitrile monomers, amide monomers and other structural units).
[0205] When the above-mentioned groups are substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom. These substituents are high-pressure-resistant substituents, which are more conducive to stabilizing the structure of the polymer. Halogen atoms may include fluorine atoms, chlorine atoms, bromine atoms, and the like.
[0206] In some embodiments, the degree of polymerization n of the ester polymer is a positive integer selected from 800 to 20,000.
[0207] Optionally, the polymerization degree n of the ester polymer is a positive integer selected from 1,000 to 15,000.
[0208] In some embodiments, the molecular weight of the ester polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.
[0209] For example, the molecular weight of the ester polymer may be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.5×10 6 g / mol or a range consisting of any two of the above values.
[0210] [Ketone-aldehyde polymers]
[0211] In some embodiments, the first polymer and the second polymer each independently include an aldehyde-ketone polymer, wherein the aldehyde-ketone polymer is made into a sheet structure; the sheet structure is (T m4 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K3, 0.8≤K3<∞, T m4 °C represents the melting temperature of the aldehyde-ketone polymer.
[0212] In some embodiments, 0.8≤K3≤100; optionally, 0.8≤K3≤10.
[0213] Illustratively, K3 may be 0.8, 0.9, 1, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000, or a range consisting of any two of the above values.
[0214] In some embodiments, the glass transition temperature of the aldehyde-ketone polymer is T g4 , its unit is ℃, -100≤T g4 ≤50; optionally, -80≤T g4 ≤30.
[0215] For example, the glass transition temperature of the aldehyde-ketone polymer may be -100°C, -90°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range consisting of any two of the above values.
[0216] In some embodiments, the aldehyde-ketone polymer comprises a structural unit represented by formula (DI),
[0217] In formula (DI), R 41 Including single bonds, substituted or unsubstituted C1-C6 methylene; R 42 including hydrogen atoms, substituted or unsubstituted C1-C6 alkyl groups;
[0218] Optionally, R 41 including single bonds, substituted or unsubstituted C1-C2 methylene groups;
[0219] Optionally, R 42 This includes hydrogen atoms, and substituted or unsubstituted C1-C3 alkyl groups.
[0220] In the embodiments of the present application, a single bond indicates that the group does not exist, and the atoms on both sides of the group are connected by a single bond, for example, R 41 is a single bond, indicating R 41 The carbon atoms on both sides are connected by single bonds.
[0221] Illustratively, the aldehyde-ketone polymer includes at least one of the structural units represented by formula (DI-1) to the structural units represented by formula (DI-6),
[0222] Illustratively, the aldehyde-ketone polymer includes a structural unit represented by formula (DII),
[0223] In formula (DII), R 43 to R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from an integer from 0 to 5, and at least one of r and s is selected from a positive integer; optionally, R 43 to R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C2 hydroxyalkyl group, or a substituted or unsubstituted C1-C2 alkoxy group.
[0224] In some embodiments, the aldehyde-ketone polymer includes at least one of the structural units represented by formula (DII-1) to the structural units represented by formula (DII-4),
[0225] The molecular chain entanglement degree of the above-mentioned aldehyde-ketone polymer is low, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte, which is conducive to forming a gel-state substance with the electrolyte.
[0226] The above-mentioned polymers are only examples of the structural groups of the main molecular chain. In the embodiments of the present application, the polymers can also be obtained by copolymerizing the above-mentioned structural groups with other types of structural groups (such as olefin structural units, ester monomers, nitrile monomers, amide monomers and other structural units).
[0227] When the above-mentioned groups are substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom. These substituents are high-pressure-resistant substituents, which are more conducive to stabilizing the structure of the polymer. Halogen atoms may include fluorine atoms, chlorine atoms, bromine atoms, and the like.
[0228] In some embodiments, the degree of polymerization n of the aldehyde-ketone polymer is a positive integer selected from 500 to 15,000.
[0229] Optionally, the degree of polymerization n of the aldehyde-ketone polymer is selected from a positive integer ranging from 500 to 10,000.
[0230] In some embodiments, the molecular weight of the aldehyde-ketone polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.
[0231] For example, the molecular weight of the aldehyde-ketone polymer may be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.0×10 6 g / mol or a range consisting of any two of the above values.
[0232] The relevant parameters of the polymer according to the embodiment of the present application can be detected by the following methods:
[0233] The groups of the polymers of the embodiments of the present application can be detected by infrared spectrophotometry IR. Specifically, the liquid-retaining polymer is tested using a Thermo Nicolet Nexus 670 attenuated total reflectance Fourier transform infrared spectrometer (FTIR-ATR), and then tested in accordance with the standard GB / T6040-2002. The test range is: ATR method 600-4000 cm -1 ; Repeatability: ±2cm -1 ; Resolution: better than 4cm -1 ; Transmission depth 0.2~0.6μm.
[0234] The structure of the polymer according to the embodiment of the present application can be tested by nuclear magnetic resonance (NMR). Specifically, 1H NMR and 13C NMR are performed on a Varian Mercury Plus-400 NMR spectrometer at a test temperature of 20° C., TMS as an internal standard, CDCl 3 as a solvent, and a proton resonance frequency of 400 MHz.
[0235] The polymer monomer type of the polymer according to the embodiment of the present application (especially suitable for monomers that account for a relatively small proportion in the polymer) can be tested by pyrolysis-gas chromatography-mass spectrometry. The specific testing steps are as follows: accurately weigh 0.5 mg of sample and put it into the sample cup. After fixing it to the injection rod, it is loaded into the pyrolyzer installed near the GC (gas chromatography) injection port. After the pyrolyzer temperature reaches the set temperature, press the injection button, and the sample cup falls rapidly into the core of the pyrolysis furnace by free fall. In the inert gas N2 atmosphere, the volatile components are instantly vaporized and carried into the gas chromatography column by the carrier gas for separation. Finally, it is detected by a flame ionization detector FID or a mass spectrometer MS to obtain a gas chromatogram or a total ion current diagram.
[0236] The molecular weight of the polymer in the embodiment of the present application has a well-known meaning in the art and can be measured using commonly used equipment and methods in the art. Gel permeation chromatography (GPC) testing can be used. The specific testing steps are as follows: take an appropriate amount of the sample to be tested (the sample concentration is sufficient to ensure 8%-12% shading), add 20 ml of deionized water, and simultaneously supercharge for 5 minutes (53 KHz / 120 W) to ensure that the sample is completely dispersed, and then measure the sample in accordance with GB / T19077-2016 / ISO 13320:2009 standard.
[0237] Alternatively, a multi-angle laser light scattering (MALLS) instrument was used for testing. Specifically, a GPC coupled with a Dawn Heleos II multi-angle laser light scattering device, an Optilab T-rEX refractive index (RI) detector, and a Visco Star II viscometer (Wyatt Technology Corporation, USA) was used. Testing was conducted at 30°C, using tetrahydrofuran as the mobile phase at a flow rate of 1.0 ml / min. SEC-SAMLL data were processed using the commercial ASTRA6 software to obtain molecular weight parameters.
[0238] In some embodiments, a polymer group is added to a first solvent at 70°C to form a polymer system; the polymer system is allowed to stand at 70°C for 8 hours and then at 25°C for ≥24 hours, and then filtered through a 200-mesh filter to leave a first substance. The mass of the polymer group is q, expressed in g; the mass of the first substance is m, expressed in g; and the polymer group and the first substance satisfy the following ratio: 5 ≤ m / q ≤ 1000. In particular, the liquid-retaining polymer satisfies the following ratio: 5 ≤ m / q ≤ 1000.
[0239] The polymer group has excellent liquid absorption and liquid retention properties, which is beneficial to improving the liquid absorption and liquid retention capabilities of the isolation membrane.
[0240] In some embodiments, 10≤m / q≤1000; further optionally, 10≤m / q≤50. For example, m / q can be 5, 10, 20, 25, 28, 30, 32, 35, 40, 50, 80, 100, 200, 500, 1000, or a range consisting of any two of the above values.
[0241] The polymer system is allowed to stand at 70°C for 8 hours and at 25°C for ≥24 hours. After undergoing two stages of standing treatment, part of the polymer system is transformed into a gel-state substance through swelling and adsorption; the polymer system comes into contact with the electrolyte, the polymer molecular chains stretch and open, the electrolyte can diffuse between the molecular chains, the polymer molecular chains swell and adsorb the electrolyte, which is beneficial to improving the liquid absorption and liquid retention capabilities of the isolation membrane, and can further enhance the cycle performance of the battery cell.
[0242] Illustratively, based on the mass of the polymer system, the ratio of the mass content of the polymer group to the mass content of the first solvent ranges from 1:100 to 1:10, for example, 3:50.
[0243] Exemplarily, the first solvent is the same as or similar to the solvent of the electrolyte, and the first solvent may include at least one of a carbonate solvent and an ether solvent. For example, the carbonate solvent includes a cyclic carbonate solvent and / or a linear carbonate solvent.
[0244] As examples of the cyclic carbonate solvent, the cyclic carbonate solvent includes one or more of ethylene carbonate EC, vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinyl ethylene carbonate VEC, and dioctyl carbonate CC.
[0245] As examples of the linear carbonate solvent, the linear carbonate solvent includes one or more of dimethyl carbonate DMC, diethyl carbonate DEC, ethyl methyl carbonate EMC, diphenyl carbonate DPC, methyl allyl carbonate MAC, and polycarbonate VA.
[0246] As examples of the ether solvent, the ether solvent includes one or more of tetrahydrofuran THF, 2-methyltetrahydrofuran 2me-thf, 1,3-dioxolane DOL, dimethoxymethane DMM, 1,2-dimethoxyethane DME, and diglyme DG.
[0247] Optionally, the first solvent may also contain a lithium salt and an electrolyte additive, such as lithium hexafluorophosphate, vinylene carbonate VC, fluorovinylene carbonate FEC, and the like.
[0248] In this application, m / q is also referred to as the precipitation value, which characterizes the ability of the polymer group and solvent to transform into a gel-state substance.
[0249] The first substance mainly includes a gel-state substance formed by a polymer group and a first solvent. In this type of gel-state substance, the molecular structure of the polymer does not substantially change.
[0250] In some embodiments, the first substance is dried at 80° C. for 12 hours to remove the first solvent in the first substance. Detection by infrared spectrophotometry (IR) or nuclear magnetic resonance (NMR) testing shows that the main component of the first substance after drying is the liquid-retaining polymer described above.
[0251] By increasing the temperature, the embodiments of this application can achieve stretching of the polymer chains within the safe operating temperature range of the battery cells, promoting mutual attraction and physical bonding between the polymer chains and the electrolyte. At room temperature, the activity of the polymer chain segments decreases, allowing them to remain attached to the separator and lock the electrolyte within the space surrounding the polymer chains, forming a gel or gel-like state. This can increase the transport rate of active ions, such as lithium ions, and improve cycling performance.
[0252] In some embodiments, the separator includes a porous substrate, and the polymer group is distributed in the pores of the porous substrate.
[0253]
[0254] In other embodiments, the separator includes a porous substrate and a polymer layer disposed on at least one surface of the porous substrate, wherein the polymer layer includes a polymer group. The polymer layer disposed on at least one surface of the porous substrate means that the polymer layer can be disposed on one surface of the porous substrate or on both surfaces of the porous substrate. The polymer group can be dispersed in a solvent to form a polymer mixture system, and the polymer mixture system can be coated on the porous substrate via a coating process such as atomized spray coating or gravure coating.
[0255] The embodiments of the present application do not particularly limit the material of the porous substrate. Any known porous substrate with good chemical and mechanical stability can be selected. For example, the porous substrate may include at least one of a porous polyolefin-based resin film (e.g., at least one of polyethylene, polypropylene, and polyvinylidene fluoride), a porous glass fiber, and a porous non-woven fabric. The porous substrate may be a single-layer film or a multi-layer composite film. When the porous substrate is a multi-layer composite film, the materials of each layer may be the same or different.
[0256] In some embodiments, the porous substrate has a porosity greater than or equal to 25%, and can optionally be between 25% and 50%. When the porosity of the porous substrate is within this range, the air permeability of the porous substrate can be increased, which is beneficial for the migration of active ions. Furthermore, due to the relatively low porosity, the mechanical properties of the porous substrate can be improved, and the porous substrate can provide good support for the polymer layer.
[0257] In some embodiments, the thickness of the porous substrate may be less than or equal to 16 μm, and may be 5 μm to 12 μm. For example, the thickness of the porous substrate may be 1 μm, 2 μm, 3 μm, 5 μm, 10 μm, 12 μm, 15 μm, 16 μm, or a range consisting of any two of the aforementioned values.
[0258] Optionally, the polymer layer includes heat-resistant particles. The synergistic effect of the heat-resistant particles and the polymer group can further enhance the overall heat resistance and ion transport properties of the separator. The polymer group and heat-resistant particles can be dispersed in a solvent to form a polymer mixture system, which is then applied to the porous substrate via a coating process such as atomized spray coating or gravure coating.
[0259] In some embodiments, based on the total mass of the polymer layer, the ratio of the mass percentage of the polymer group to the mass percentage of the heat-resistant particles is (0.2 to 5.0):1, or optionally (0.5 to 2.0):1. When the contents of the heat-resistant particles and the polymer group are within the above ranges, the heat resistance and ion transport properties of the separator can be further improved. Exemplarily, the ratio of the mass percentage of the polymer group to the mass percentage of the heat-resistant particles can be 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.8:1, 1.0:1, 1.2:1, 1.5:1, 1.8:1, 2.0:1, 2.5:1, 2.8:1, 3.0:1, 3.2:1, 3.5:1, 3.8:1, 4.0:1, 4.2:1, 4.5:1, 4.8:1, 5.0:1 or a range consisting of any two of the above values.
[0260] In some embodiments, the thickness of the polymer layer may be 0.5 μm to 3.0 μm; optionally, 1.0 μm to 2.0 μm. When the thickness of the polymer layer is within the above range, the heat resistance and ion transmission performance of the isolation membrane as a whole can be further improved. For example, the thickness of the polymer layer may be 0.5 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.3 μm, 2.5 μm, 2.8 μm, 3.0 μm, or a range consisting of any two of the above values.
[0261] Optionally, the separator may further include a heat-resistant coating, wherein the heat-resistant coating is located on at least one surface of the porous substrate, and the polymer layer is located on a side of the heat-resistant coating facing away from the porous substrate.
[0262] The heat-resistant coating may include heat-resistant particles. In some embodiments, the heat-resistant particles include at least one of inorganic particles and organic particles. By adding heat-resistant particles, the heat resistance of the isolation film can be improved.
[0263] In some embodiments, the mass percentage of the inorganic particles in the heat-resistant coating is ≤ 30. For example, the mass percentage of the inorganic particles in the heat-resistant coating is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, or a range consisting of any two of the above values.
[0264] The inorganic particles may include at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having the ability to transport active ions, and inorganic particles capable of electrochemical oxidation and reduction.
[0265] In some embodiments, inorganic particles having a dielectric constant of 5 or higher may include boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), silicon oxide SiO x (0<x≤2), tin dioxide (SnO2), titanium oxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), hafnium dioxide (HfO2), cerium oxide (CeO2), zirconium titanate (ZrTiO3), barium titanate (BaTiO3), magnesium fluoride (MgF2), Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti n O3 (abbreviated as PLZT, 0<m<1, 0<n<1) and Pb(Mg3Nb 2 / 3 ) at least one of O3-PbTiO3 (abbreviated as PMN-PT).
[0266] In some embodiments, the inorganic particles capable of transporting active ions may include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0<x<2, 0<y<3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0<x<2, 0<y<1, 0<z<3), (LiAlTiP) x O y Glass-like (0<x<4, 0<y<13), lithium lanthanum titanate (Li x La y TiO3, 0<x<2, 0<y<3), lithium germanium thiophosphate (Li x Ge y P z S w, 0<x<4, 0<y<1, 0<z<1, 0<w<5), lithium nitride (Li x N y , 0<x<4, 0<y<2), SiS2 type glass (Li x Si y S z , 0<x<3, 0<y<2, 0<z<4) and P2S5 type glass (Li x P y S z , 0<x<3, 0<y<3, 0<z<7).
[0267] In some embodiments, the inorganic particles capable of electrochemical oxidation and reduction may include at least one of lithium-containing transition metal oxides, lithium-containing phosphates with olivine structures, carbon-based materials, silicon-based materials, tin-based materials, and lithium titanium compounds.
[0268] In some embodiments, the heat-resistant coating may also include other organic particles, for example, the organic particles may include polystyrene, polyethylene, polyimide, melamine resin, phenolic resin, polypropylene, polyester (such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate), polyphenylene sulfide, polyaramid, polyamideimide, polyimide, copolymer of butyl acrylate and ethyl methacrylate and mixtures thereof.
[0269] In some embodiments, the heat-resistant coating may further include a binder. For example, the binder may include at least one of an aqueous solution-based acrylic resin (e.g., a homopolymer of acrylic acid, methacrylic acid, or sodium acrylate monomers, or a copolymer with other comonomers), polyvinyl alcohol (PVA), an isobutylene-maleic anhydride copolymer, and polyacrylamide.
[0270] In some embodiments, the thickness of the heat-resistant coating is ≤ 4 μm. This helps to increase the energy density of the battery cell. In the embodiments of the present application, the thickness of the heat-resistant coating refers to the thickness of the heat-resistant coating located on a single side of the substrate. For example, the thickness of the heat-resistant coating can be 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, or a range consisting of any two of the above values.
[0271] In some embodiments, the coating weight of the polymer group is 0.5 mg / 1540.25 mm 2 Up to 5mg / 1540.25mm 2 .
[0272] When the coating weight is within the above range, the ability to form a gel-like substance with the electrolyte can be further improved, thereby increasing the liquid absorption rate.
[0273] Optionally, the coating weight of the polymer group is 0.5 mg / 1540.25 mm 2 Up to 3.5mg / 1540.25mm 2 .
[0274] For example, the coating weight of the liquid-retaining polymer per unit area of the isolation film may be 0.5 mg / 1540.25 mm 2 、0.8mg / 1540.25mm 2 、1.0mg / 1540.25mm 2 、1.2mg / 1540.25mm 2 、1.3mg / 1540.25mm 2 、1.5mg / 1540.25mm 2 、2.0mg / 1540.25mm 2 , 2.2mg / 1540.25mm 2 , 2.5mg / 1540.25mm 2 、3mg / 1540.25mm 2 、3.5mg / 1540.25mm 2 、4mg / 1540.25mm 2 4.5mg / 1540.25mm 2 、5mg / 1540.25mm 2 , or a range consisting of any two of the above values.
[0275] In the embodiment of the present application, the coating weight refers to the coating weight of the liquid-retaining polymer on one side of the isolation film, which can be detected by using equipment and methods known in the art, for example, by cutting the same mother roll substrate and isolation film into 1540.25mm 2 The weight of 10 isolation film discs is respectively weighed, and the coating weight of the highly liquid-absorbent polymer in the isolation film can be obtained by calculation.
[0276] battery cells
[0277] In the second aspect, an embodiment of the present application proposes a battery cell, which includes an electrode assembly and an electrolyte, the electrode assembly includes a positive electrode sheet, a negative electrode sheet and an isolation membrane, the isolation membrane is arranged between the positive electrode sheet and the negative electrode sheet, and the isolation membrane includes an isolation membrane as in any embodiment of the first aspect of the present application.
[0278] [Positive electrode]
[0279] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector.
[0280] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on either or both of the two facing surfaces of the positive electrode current collector.
[0281] The positive electrode active material layer includes a positive electrode active material, which can be a positive electrode active material commonly known in the art for use in battery cells. For example, the positive electrode active material can include at least one of the following materials: a lithium-containing phosphate compound, a lithium-containing transition metal oxide, a sodium-containing phosphate compound, and a sodium-containing transition metal oxide.
[0282] For example, the general formula of the olivine-type phosphate active material (lithium-containing phosphate compound) is: Li x A y Me a M b P 1-c X c Y z , wherein 0≤x≤1.3, 0≤y≤1.3, and 0.9≤x+y≤1.3; 0.9≤a≤1.5, 0≤b≤0.5, and 0.9≤a+b≤1.5; 0≤c≤0.5; 3≤z≤5; A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of S, Si, Cl, B, C, and N; and Y includes one or more of O and F. Specifically, the olivine-type phosphate active material includes one or more of LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.
[0283] For example, lithium transition metal oxides (layered materials such as ternary, lithium nickelate / sodium, lithium cobaltate / sodium, lithium manganate / sodium, lithium-rich layered and rock salt phase layered materials). The general formula of the layered structure positive electrode active material is: Li x A y Ni a Co b Mn c M (1-a-b-c) Y z, wherein 0≤x≤2.1, 0≤y≤2.1, and 0.9≤x+y≤2.1; 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0.1≤a+b+c≤1; 1.8≤z≤3.5; A includes one or more of Na, K, and Mg; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; Y includes one or more of O and F. Optionally, y=0. Specifically, the layered structure positive electrode active material may include lithium cobalt oxide LCO, lithium nickel oxide LNO, lithium manganese oxide LMO, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333),LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622),LiNi 0.8 Co 0.1 Mn 0.1 One or more of O2 (NCM811) and NCA.
[0284] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil or an aluminum alloy foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include a combination of one or more selected from aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. The polymer material base layer may include a combination of one or more selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0285] In some embodiments, the positive electrode active material layer may further optionally include a positive electrode conductive agent. The present application does not particularly limit the type of positive electrode conductive agent. For example, the positive electrode conductive agent may include a combination of one or more selected from superconducting carbon, conductive carbon black, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the positive electrode conductive agent is less than 5% based on the total mass of the positive electrode active material layer.
[0286] In some embodiments, the positive electrode active material layer may also optionally include a positive electrode binder. The embodiments of the present application do not particularly limit the type of positive electrode binder. As an example, the positive electrode binder may include a combination of one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin. In some embodiments, based on the total mass of the positive electrode active material layer, the mass percentage of the positive electrode binder is less than 5%. Compared to the crystallinity of the fluoropolymer of the embodiment of the present application, the crystallinity of the positive electrode binder is higher. Compared to the melting temperature of the fluoropolymer of the embodiment of the present application, the melting temperature of the positive electrode binder is higher.
[0287] The positive electrode active material layer is typically formed by coating a positive electrode slurry onto a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent can be, but is not limited to, N-methylpyrrolidone (NMP). Of course, the preparation of the positive electrode sheet is not limited to the above method; the preparation methods described above can also be used.
[0288] [Negative electrode]
[0289] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material.
[0290] Illustratively, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is disposed on either or both of the two facing surfaces of the negative electrode current collector.
[0291] The negative electrode active material can be any negative electrode active material known in the art for use in battery cells. For example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, a silicon-carbon composite, a silicon-nitrogen composite, and a silicon alloy. The tin-based material may include at least one of elemental tin, tin oxide, and a tin alloy.
[0292] In some embodiments, the negative electrode active material layer may further optionally include a negative electrode conductive agent. The present embodiments do not particularly limit the type of the negative electrode conductive agent. For example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the negative electrode conductive agent is ≤5% based on the total mass of the negative electrode active material layer.
[0293] In some embodiments, the negative electrode active material layer may further optionally include a negative electrode binder. The present application embodiment does not particularly limit the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage of the negative electrode binder based on the total mass of the negative electrode active material layer is ≤5%.
[0294] In some embodiments, the negative electrode active material layer may optionally include other additives. For example, these additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, and the like. In some embodiments, the weight percentage of these other additives is ≤ 2% based on the total weight of the negative electrode active material layer.
[0295] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, a copper alloy, nickel, a nickel alloy, titanium, a titanium alloy, silver, and a silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0296] The negative electrode active material layer is typically formed by coating a negative electrode slurry onto a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is typically formed by dispersing the negative electrode active material, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water. Of course, the preparation of the negative electrode sheet is not limited to the above method; the preparation methods described above may also be used.
[0297] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode active material layer. For example, in some embodiments, the negative electrode plate described herein further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode active material layer and disposed on the surface of the negative electrode current collector. In other embodiments, the negative electrode plate described herein further includes a protective layer covering the surface of the negative electrode active material layer.
[0298] [Electrolytes]
[0299] During the charge and discharge process of a battery cell, active ions are embedded and released back and forth between the positive and negative electrodes, and the electrolyte conducts the active ions between the positive and negative electrodes. This application does not specifically limit the type of electrolyte, and it can be selected according to actual needs.
[0300] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not particularly limited and can be selected according to actual needs.
[0301] When the battery cell of the present application is a lithium-ion battery, as an example, the electrolyte salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0302] When the battery cell of the present application is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).
[0303] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), diethyl sulfone (ESE), tetrahydrofuran THF, 2-methyltetrahydrofuran 2me-thf, 1,3-dioxolane DOL, dimethoxymethane DMM, 1,2-dimethoxyethane DME, and diethylene glycol dimethyl ether DG.
[0304] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.
[0305] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly through a winding process and / or a lamination process.
[0306] In some embodiments, the battery cell may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0307] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0308] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process or a lamination process.
[0309] The present application has no particular limitation on the shape of the battery cell, which can be cylindrical, square or any other shape. FIG1 shows a battery cell 5 with a square structure as an example.
[0310] In some embodiments, as shown in Figures 1 and 2, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.
[0311] The manufacturing method of the battery cell of the present application is well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, separator, and negative electrode sheet can be wound or laminated to form an electrode assembly. The electrode assembly is then placed in an outer packaging, dried, and then injected with electrolyte. The battery cell is then vacuum packaged, allowed to stand, formed, and shaped to obtain a battery cell.
[0312] In some embodiments of the present application, the battery cells according to the present application can be assembled into a battery module. The battery module can contain multiple battery cells, and the specific number can be adjusted according to the application and capacity of the battery module.
[0313] Figure 3 is a schematic diagram of an exemplary battery module 4. As shown in Figure 3 , within the battery module 4, multiple battery cells 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple battery cells 5 may be secured together using fasteners.
[0314] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of battery cells 5 are accommodated in the accommodation space.
[0315] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0316] Both the battery module 4 and the battery pack can be used as specific examples of batteries in the embodiments of the present application.
[0317] Figures 4 and 5 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 4 and 5, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 covers the lower case 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0318] Electrical devices
[0319] In a third aspect, the present application provides an electrical device, which includes at least one of the battery cells, battery modules, and battery packs of the present application. The battery cells, battery modules, and battery packs can be used as power sources for the electrical device, or as energy storage units for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.
[0320] The electric device can select a battery cell, battery module or battery pack according to its usage requirements. Figure 6 is a schematic diagram of an electric device as an example. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the electric device, a battery pack 1 or a battery module can be used. As another example, the electric device can be a mobile phone, a tablet computer, a laptop computer, etc. The electric device usually requires to be lightweight and thin, and a battery cell can be used as a power source.
[0321] Example
[0322] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0323] Example 1 Preparation of lithium-ion battery
[0324] (1) Preparation of positive electrode sheet:
[0325] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.
[0326] The positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), conductive carbon black, and binder polyvinylidene fluoride (PVDF) are thoroughly stirred in an appropriate amount of N-methylpyrrolidone (NMP) to create a positive electrode slurry. The mass ratio of NCM622, conductive carbon black, and PVDF in the positive electrode slurry is 97.5:1.4:1. The positive electrode slurry is coated on a current collector aluminum foil and vacuum-dried at 100°C before cold pressing. The sheet is then trimmed, cut, and slit, and then dried at 85°C under vacuum for 4 hours to form the positive electrode sheet.
[0327] (2) Preparation of negative electrode sheet:
[0328] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.
[0329] The negative electrode active material (artificial graphite), conductive agent (carbon black), binder (styrene-butadiene rubber (SBR), and thickener (sodium carboxymethyl cellulose (CMC)) were mixed uniformly in a weight ratio of 97.4:2:0.5:0.1 and added to deionized water to form the negative electrode slurry. The negative electrode slurry was coated on the current collector copper foil and dried at 85°C. After cold pressing, trimming, cutting, and slitting, the negative electrode sheet was dried at 120°C under vacuum for 12 hours.
[0330] (3) Preparation of electrolyte:
[0331] In an environment with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate are mixed in a volume ratio of 1:1:1 to obtain an electrolyte solvent, and then the lithium salt LiPF6 is mixed with the mixed solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0332] (4) Preparation of isolation membrane
[0333] A 7 μm polyethylene film (PE) was used as the substrate.
[0334] The polymer components are dispersed in dimethyl carbonate (DMC) solvent to form a mixed system, and the mixed system is sprayed onto both surfaces of the polyethylene film to form polymer layers. The atomizing solvent is water, and the mass content of the mixed system is 1%.
[0335] (5) Preparation of lithium-ion batteries:
[0336] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive electrode sheet and the negative electrode sheet to serve as an isolation, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, dried, and then injected with electrolyte, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0337] Comparative Example 1
[0338] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the separator in Comparative Example 1 was a polyethylene film (PE) with a thickness of 7 μm.
[0339] Comparative Example 2 and Comparative Example 3
[0340] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the materials of the polymer group of the isolation membranes in Comparative Examples 2 and 3 were changed.
[0341] Example 1-2 to Example 1-6
[0342] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the coating weight of the polymer group in the polymer layer of the separator in Examples 1-2 to 1-6 was adjusted.
[0343] Example 2-1 to Example 2-3
[0344] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the types of polymer groups in the polymer layers of the separators in Examples 2-1 and 2-3 were adjusted.
[0345] Example 3-1
[0346] A lithium-ion battery was prepared using a method similar to that of Example 1. Unlike Example 1, Example 3-1 adjusted the position of the polymer layer of the separator. Specifically, the steps of preparing the separator included:
[0347] 7μm polyethylene film (PE) was used as the separator substrate;
[0348] The silicon oxide particles and the binder aqueous solution type polyacrylic acid are uniformly mixed in an appropriate amount of solvent deionized water at a mass ratio of 20:80 to obtain a coating slurry.
[0349] The prepared coating slurry was applied on both surfaces of a PE substrate using a coater to form a heat-resistant coating.
[0350] The polymer group and the binder are dispersed in dimethyl carbonate (DMC) solvent to form a mixed system, and the mixed system is atomized and sprayed on the surface of the heat-resistant coating to form a polymer layer, thereby obtaining an isolation film.
[0351] Example 3-2 to Example 3-5
[0352] A lithium-ion battery was prepared using a method similar to that of Example 1. Unlike Example 1, Examples 3-3-2 to 3-5 adjusted the preparation method of the isolation membrane. Specifically, the steps of preparing the isolation membrane included:
[0353] 7μm polyethylene film (PE) was used as the separator substrate;
[0354] The polymer group, the silicon oxide particles, and the binder aqueous solution type polyacrylic acid are uniformly mixed in an appropriate amount of solvent deionized water at a mass ratio of 80:20 to obtain a coating slurry.
[0355] The prepared coating slurry was applied on both surfaces of a PE substrate using a coater to form a heat-resistant coating.
[0356] The polymer group and the binder are dispersed in dimethyl carbonate (DMC) solvent to form a mixed system, and the mixed system is atomized and sprayed on the surface of the heat-resistant coating to form a polymer layer, thereby obtaining an isolation film.
[0357] In Example 3-2, the mass ratio of the polymer group to the silicon oxide compound particles is 1.5:1.
[0358] In Example 3-3, the mass ratio of the polymer group to the silicon oxide compound particles is 0.5:1.
[0359] In Examples 3-4, the mass ratio of the polymer group to the silicon oxide compound particles is 2:1.
[0360] In Examples 3-5, the mass ratio of the polymer group to the silicon oxide compound particles is 0.2:1.
[0361] In Examples 3-5, the mass ratio of the polymer group to the silicon oxide compound particles is 0.5:1.
[0362] The data of the examples and comparative examples are shown in Table 1.
[0363] Test section
[0364] 1. Lithium-ion battery performance (cycle test under high clamp force)
[0365] Before cycling the battery, apply a preload of 10,000 N to the cell. At 25°C, charge the lithium-ion battery at a constant current of 1C to 4.25V, then charge at a constant voltage of 4.25V to a current of 1C, and then discharge at a constant current of 1C to 2.8V. This constitutes one charge-discharge cycle. Taking the initial discharge capacity as 100%, calculate the capacity retention rate after 1,000 cycles. Capacity retention rate after 1,000 cycles (%) = discharge capacity at the 1,000th cycle / initial discharge capacity × 100%.
[0366] 2. Test of isolation membrane parameters
[0367] Test of the isolation film quality M: Use a cutting machine to cut 10 pieces with an area of 1540.25mm 2 The isolation membrane is placed on an electronic balance and weighed. The weight of the isolation membrane is recorded as M.
[0368] M1 test: The area of 10 cut pieces is 1540.25mm 2 The isolation membrane was placed in 10 mL of 1 M LiPF6 and EC, EMC and DMC electrolytes with a volume ratio of 1:1:1 for 2 h, taken out and suspended for 2 min, weighed with an electronic balance, and recorded as m1;
[0369] The liquid retention rate was calculated as (m1-M) / M×100%.
[0370] m2 test: Place the separator soaked in electrolyte in a pressure device, pressurize to 10000N, maintain pressure for 5 minutes, take out the electronic balance and weigh it, and record it as m2;
[0371] The liquid retention rate after pressurization is calculated as: (m2-M) / M×100%.
[0372] The liquid retention capacity is: Λ = (m2-M) / (m1-M)×100%.
[0373] Test results
[0374] The test results are shown in Table 1 and Table 2.
[0375] Table 1
[0376] In Table 1, 75% VDF means that the molar percentage of vinylidene fluoride VDF is 75% based on the total molar amount of vinylidene fluoride VDF, hexafluoropropylene HFP and ethylene.
[0377] Table 2
[0378] In Table 2, the liquid retention capacity
[0379] The liquid retention rate (before pressurization) is (m1-M) / M×100%.
[0380] The liquid retention rate (after pressurization) is (m2-M) / M×100%.
[0381] Compared with Comparative Example 1, the embodiment of the present application adds the polymer of the present application to the separator, and the cycle performance of the lithium-ion battery is improved.
[0382] Although polymers are added to the separators in Comparative Examples 2 and 3, the polymers have poor liquid retention and liquid absorption capabilities and cannot effectively improve the cycle performance of the lithium-ion battery.
[0383] Compared with Comparative Example 1, a polymer layer is provided on the surface of the separator in the embodiment of the present application. The introduction of the polymer can increase the liquid absorption rate and liquid retention capacity of the separator, and can further improve the cycle performance of the battery cell.
[0384] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and components may be substituted with equivalents without departing from the scope of the present application. In particular, the various technical features described in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but encompasses all technical solutions within the scope of the claims.
Claims
1. A separator, comprising a polymer group, wherein the polymer group comprises at least one of a first polymer and a second polymer, in, The isolation film satisfies: M represents the mass of the separator that does not absorb the electrolyte, and its unit is g; m1 represents the mass of the isolation membrane weighed at ambient pressure after being immersed in the electrolyte for 2 hours, and its unit is g; m2 represents the mass of the isolation membrane weighed at a pressure of 10000N in ambient pressure after the isolation membrane is immersed in the electrolyte for 2 hours, and its unit is g; v represents the liquid absorption rate of the isolation membrane, and its unit is mg / s; λ represents the porosity of the separator.
2. The isolation film according to claim 1, wherein: The isolation film satisfies:
3. The isolation film according to claim 1 or 2, wherein: The isolation film satisfies: Optionally, 4. The separator according to any one of claims 1 to 3, wherein: The isolation film satisfies:
5. The separator according to any one of claims 1 to 4, wherein: The isolation film satisfies:
6. The separator according to any one of claims 1 to 5, wherein: The isolation film satisfies: v / λ>5.00; optionally, 5<v / λ<50.
7. The separator according to any one of claims 1 to 6, wherein: Based on the total mass of the isolation film, the mass percentage of the polymer group is 0.1% to 20%.
8. The separator according to any one of claims 1 to 7, wherein: The first polymer and the second polymer each independently comprise a fluorinated polymer; Optionally, the crystallinity of the fluorinated polymer measured by differential scanning calorimetry is Xc1, 0<Xc1≤30%; The melting temperature of the fluorinated polymer is T m1 , its unit is ℃, 0<T m1 ≤140; Further optionally, the glass transition temperature of the fluorinated polymer is T g1 , the unit is ℃, -150≤T g1 ≤60; Further optionally, the fluorinated polymer comprises at least one of the structural units represented by formula (AI) to the structural units represented by formula (AIII), In formula (AI) and formula (AII), R 11 , R 12 , R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 , R 12 , R 13 and R 14 At least one of them contains a fluorine atom; In formula (AIII), R 15 Including a single bond, a substituted or unsubstituted C1-C3 alkyl group; p is selected from a positive integer from 1 to 3; n is selected from a positive integer from 1000 to 30000.
9. The battery cell according to any one of claims 1 to 8, wherein: The first polymer and the second polymer each independently comprise an ether polymer, Optionally, the ether polymer is made into a sheet structure; the sheet structure is (T m2 The elastic modulus G'-energy loss modulus G" curve is obtained by dynamic frequency scanning test at +20)℃, and the slope of the elastic modulus G'-energy loss modulus G" curve is K1, 1<K1<∞, T m2 ℃ represents the melting temperature of the ether polymer; Further optionally, the ether polymer comprises at least one of the structural unit represented by formula (BI) and the structural unit represented by formula (BII), In formula (BI), R 21 and R 22 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; R 23 Including substituted or unsubstituted C1-C5 alkylene; In formula (BII), R 24 To R 27 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 alkoxy group or an ether group, and R 24 To R 27 At least one of them contains a substituted or unsubstituted C1-C3 alkoxy group or an ether group.
10. The battery cell according to any one of claims 1 to 9, wherein: The first polymer and the second polymer each independently include the ester polymer; Optionally, the ester polymer is made into a sheet-like structure; the sheet-like structure is (T m3 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency scanning test at 20 °C. The slope of the elastic modulus G'-energy loss modulus G" curve is K2, 1<K2<∞, T m3 ℃ represents the melting temperature of the ester polymer; optionally, 1< K2≤100; further optionally, 1<K2≤10; Further optionally, the ester polymer includes at least one of the structural unit represented by formula (CI) and the structural unit represented by formula (CII), In formula (CI), R 31 , R 32 and R 33 Each independently includes a hydrogen atom, or a substituted or unsubstituted C1-C8 alkyl group; R 34 Including substituted or unsubstituted C1-C8 alkyl, or substituted or unsubstituted C1-C8 hydroxyalkyl; In formula (CII), R 35 including substituted or unsubstituted C2-C6 methylene; optionally, R 35 Each independently includes a substituted or unsubstituted C2-C4 methylene group.
11. The battery cell according to any one of claims 1 to 10, wherein: The first polymer and the second polymer each independently comprise an aldehyde ketone polymer, Optionally, the aldehyde-ketone polymer is made into a sheet-like structure; the sheet-like structure is (T m4 The elastic modulus G'-energy loss modulus G" curve is obtained by dynamic frequency scanning test at 20 ° C. The slope of the elastic modulus G'-energy loss modulus G" curve is K3, 0.8≤K3<∞, T m4 ℃ represents the melting temperature of the aldehyde-ketone polymer; Optionally, 0.8≤K3≤100; further optionally, 0.8≤K3≤10; Further optionally, the aldehyde-ketone polymer comprises at least one of the structural unit represented by formula (DI) and the structural unit represented by formula (DII), In formula (DI), R 41 Including single bonds, substituted or unsubstituted C1-C6 methylene; R 42 Including hydrogen atom, substituted or unsubstituted C1-C6 alkyl; In formula (DII), R 43 To R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s each independently is an integer selected from 0 to 5, and at least one of r and s is selected from a positive integer.
12. The separator according to any one of claims 1 to 11, wherein: The isolation membrane includes a porous substrate and a polymer layer disposed on at least one surface of the porous substrate, wherein the polymer layer includes the polymer group.
13. The separator according to any one of claims 1 to 12, wherein: The coating weight of the polymer group is 0.5 mg / 1540.25 mm 2 Up to 5mg / 1540.25mm 2 . 14 . A battery cell comprising the separator according to claim 1 .
15. A battery comprising the battery cell according to claim 14.
16. An electrical device comprising the battery according to claim 15.